Peningkatan Akses Informasi Masyarakat Melalui Pembuatan Website Desa Turirejo, Gresik - Mohammad Ilyas Aminulloh, Ilyas; Aminulloh, Mohammad Ilyas; Widodo, David Wahyu; Ivananda, Muhammad Hilmi; Mahendra, Zidan Bayu; Retnawati, Lestari (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2025)
Turirejo Village, Gresik, faces challenges in delivering information to its residents. The lack of access to important information causes limitations in community participation and appropriate decision-making. The purpose of this service is to improve access to information and community participation in Turirejo Village through the creation of a village website. The methods used include needs analysis, design, creation, and training on the use of the website to village officials and the community. The result of this activity is the creation of a website that functions as an effective means of information and communication between village officials and the community. This website provides various important information such as village news, activities, announcements. In addition, the training provided to village officials and the community improved their ability to manage and utilise the website independently. Thus, this project not only created a digital communication tool but also empowered the community in using information technology.